Análisis de la ordenanza que garantiza los derechos del adulto mayor en el sector urbano de Loja - Granda Lima, Frans Andrés (2024)
The general objective of the research work is to analyze the compliance with the ordinance that guarantees the rights of the elderly in the urban parishes of the city of Loja. The specific objectives focused on diagnosing the current situation of the ordinance and the actions taken by the GAD of Loja in favor of the elderly. In this sense, programs, services and resources for this age group were examined. Subsequently, we proceeded to determine the effectiveness and compliance with the municipal ordinance for the benefit of the elderly. To this end, the ordinance was evaluated in terms of its practical application and the degree to which its provisions are complied with. Finally, a concrete proposal was formulated to improve the deficiencies identified in the ordinance. were carefully analyzed, proposing specific recommendations to address these deficiencies and strengthen the protection and well-being of older adults in Loja canton. The methodology adopted was based on a mixed approach combining qualitative and quantitative elements. The research process was guided by deductive, analytical and synthetic methods. For data collection, various techniques adapted to the objectives of the study were used. The results obtained, together with their corresponding discussion, conclusions and recommendations, revealed a significant problem: a high degree of ignorance of the ordinance among older adults. This finding highlights the urgent need to improve the implementation and communication of the ordinance, especially considering that it targets a vulnerable age group.